Drink spiking and predatory drugging: a modern history - Donovan, Pamela (Palgrave Macmillan, 2016)
This book analyses common perceptions about drink spiking, a pervasive fear for many and sometimes a troubling reality. Ideas about spiked drinks have shaped the way we think about drugs, alcohol, criminal law, risk, nightspots, and socializing for over 150 years, since the rise of modern anaesthesia and synthetic 'pharma-ubiquity'. The book offers a wide-ranging look at the constantly shifting cultural and gender politics of 'psycho-chemical treachery'. It provides rich case histories, assesses evolving scientific knowledge, and analyzes the influence of social forces as disparate as Temperance and the acid enthusiasts of the 1960s. Drawing on interdisciplinary research, the book will be of great interest to upper-level students and scholars of criminal law, forensic science, public health, and social movements